O conflito entre o paganismo, o judaísmo e o cristianismo no principado: um estudo a partir do Contra Celso, de Orígenes - Soares, Carolline da Silva (2011)
This dissertation concerns about the socio-political and religious conflict between paganism, Judaism and Christianity, in the Roman Empire during the time of the Principatus (centuries I-III). This conflict is presented in a unique way in a work entitled Against Celsus, of the Christian priest Origen, dating from the third century A.D. This work of Origen appears as an apology is a refutation at the composition of the pagan philosopher Celsus, entitled True Word (?????? ?????). The philosopher, as a member and representative of the pagan Greco-Roman elite of the second century A.D., vehemently attacked Christianity and Judaism. The ?????? ????? of Celso is accessible to us today only by the refutation of Origen that, to answer charges of pagans transcribed several excerpts from the True Word in his apology. The hypotheses of our study are related to two main ideas: 1) the paganism and, especially, the Judaism are the main otherness front of the primitive Christianity, which Origen worked to coin a distinct Christian identity of Jews and pagans; and, 2) the so-called Judaizers in the III century, represented the main obstacle, according to the priest, for the establishment of a Christian identity more consolidated, as the Judaizers were individuals located on the border between Christianity and Judaism. Moreover, we state that the issue between Christianity, Judaism and paganism in Against Celsus contributed to the defense and the establishment of Christian and pagan identities at the time of the Principatus.